Traditional Javanese Ethnic Songs: The Supporting Aspects of its Existence in the Local Community - Wadiyo, Wadiyo; Haryono, Slamet; Wiyoso, Joko (Journal of Urban Culture Research, 2022)
This study reveals the supporting aspects that make traditional Javanese songs preserved in the community the splendor of modern Javanese songs. This research applies qualitative design with a phenomenological approach. The research location is in Central Java. The researchers collected the data by observing, interviewing and collecting documents. The researchers validate the data based on triangulation system with interactive analysis. The results find that traditional Javanese songs still exist in its local society due to the strong psychological bonding of the society with their culture. Through traditional Javanese songs, cultural messages can be conveyed beautifully, inspire imagination and impart enjoyable feelings. The implication of the research findings is the significance of traditional Javanese songs to be used as a means to foster the development of the society and the culture concerned.